Characterization of hyperchaotic states in the parameter-space of a modified Lorenz system - Correia M.J.* (2011)
In this paper we report a new four-dimensional autonomous system, constructed from a Lorenz system by introducing an adequate feedback controller to the third equation. We use a numerical method that considers the second largest Lyapunov exponent value as a measure of hyperchaotic motion, to construct a two-dimensional parameter-space color plot for this system. Different levels of hyperchaos are represented in this plot by a continuously changing yellow-red scale. Practical applications of this plot includes, by instance, walking in the parameter-space of hyperchaotic systems along suitable paths. © Published under licence by IOP Publishing Ltd.